2017
DOI: 10.1080/09658211.2017.1317814
|View full text |Cite
|
Sign up to set email alerts
|

The weapon focus effect is weaker with Black versus White male perpetrators

Abstract: We compared the influence of a weapon's presence on eyewitnesses' memory for a White versus a Black male perpetrator. Prior data indicate that unusual objects in visual scenes attract attention and that a weapon's effect depends on how unusual it seems within the context in which it appears. Therefore, given the stereotype linking Black men and weapons, we predicted a weaker weapon focus effect with the Black perpetrator. The results of Experiment 1 supported this hypothesis using White and Black witnesses. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(39 citation statements)
references
References 40 publications
1
33
5
Order By: Relevance
“…Given the uniform pattern of findings regarding faster shoot decisions (respectively slower non-shoot decisions) for Black compared to White targets in lay populations, it is important to gain further insights into the underlying procedural architecture of this effect. Some authors have pointed to the relevance that Black people are stereotypically associated with threat, danger, and crime (Eberhardt et al, 2004;Lundberg et al, 2018;Pickel & Sneyd, 2018) which is considered as an explanation for the racial bias in the shooter paradigm (Correll et al, 2011;Plant et al, 2011). From the perspective of cultural stereotypes about outgroups, the activation of a group category (which is stereotypically perceived as threatening) facilitates aggressive and stereotype-consistent responses.…”
Section: Stereotypes and Intergroup Processes Behind The Shooter Biasmentioning
confidence: 99%
“…Given the uniform pattern of findings regarding faster shoot decisions (respectively slower non-shoot decisions) for Black compared to White targets in lay populations, it is important to gain further insights into the underlying procedural architecture of this effect. Some authors have pointed to the relevance that Black people are stereotypically associated with threat, danger, and crime (Eberhardt et al, 2004;Lundberg et al, 2018;Pickel & Sneyd, 2018) which is considered as an explanation for the racial bias in the shooter paradigm (Correll et al, 2011;Plant et al, 2011). From the perspective of cultural stereotypes about outgroups, the activation of a group category (which is stereotypically perceived as threatening) facilitates aggressive and stereotype-consistent responses.…”
Section: Stereotypes and Intergroup Processes Behind The Shooter Biasmentioning
confidence: 99%
“…For example, exposure to Black faces prior to presenting images of objects increases accuracy at object categorization judgments when the subsequent object is a weapon compared to a non-weapon object, whereas this association is weaker when weapons are preceded by White faces (see Payne, 2006 , for a review). More recently, investigation in eyewitness memory has found that the so-called weapon focus effect , wherein post-event identification of criminal perpetrators holding weapons is less accurate than identifications when a weapon is not present during the crime (e.g., Erickson et al, 2014 ), is ameliorated when the perpetrator is an Black male, and more so when he wears stereotypic “hip-hop” clothing (Pickel & Sneyd, 2017 ). Taken together, these findings present a stable, replicable tendency to associate male Black faces with aggression.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the usualness that describes a suitability from the quotidian context modulates the attentional bias. In fact, some studies have demonstrated that the presence of a usual weapon attenuated the weapon focus effect (e.g., Pickel, 1999; Pickel & Sneyd, 2018). Therefore, it is hypothesized that usual weapons may attenuate such attentional bias as they will be identified as daily tools and not as a threat.…”
Section: Introductionmentioning
confidence: 99%